PROGRAM SMART CITY DI KOTA MAKASSAR PERSPEKTIF SIYASAH DUSTURIYAH - Savana Zalsabilah; Khalik, Subehan (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2025)
This research aims to examine the Smart City Program in the city of Makassar from Siyasah Dusturiyah’s perspective. The problem in this research is that the implementation of the Smart City Program is not carried out in accordance with the principles of state government administration. This research is descriptive field research. The approach used in this research is a normative juridical approach and a syar’i approach. The data used is primary legal data and secondary legal data. Data was obtained through observation, interviews and documentation, then data processing and analysis was carried out. The results of this research show that The failure to evaluate the Tourism Alley and Healthy Alley Program with RT, RW and local community leaders as interested parties has resulted in the Bara Baraya Subdistrict Government being unable to find a formulation of methods for socializing and educating the Smart City program in the Smart sector. The right environment. The obligation for the community to participate in two-way communication with the government in order to carry out the management of government affairs for the sake of realizing the benefit of the people is regulated in QS al-Imran/3: 104. The community as a group of people has an obligation to convey goodness in order to achieve ma’ruf in the form of environmental cleanliness. given space by the Bara Baraya Subdistrict Government so that the Bara Baraya Subdistrict area can avoid evil in the form of not achieving a Smart Environment as part of a Smart City.